Ceramic-Based Microfluidic Device for Separation of Magnetic Particles in Continuous Flow - Seon, Ji-Yun; Joon Yoon, Young; Yeon Cho, Kwang; Kim, Chang-Yeol; Kim, Jong-Hee; Tae Kim, Hyo (Asian Journal of Chemistry, 2014)
A ceramic-based microfluidic biochip for the application to separate the magnetic particles in the continuous flow was fabricated. To realize the various functions in a biochip, passive mixer, passive filter and active separator was integrated. Active separation was performed by external permanent magnet. A ceramic-based microfluidic chip was fabricated by LTCC (low temperature co-fired ceramic) process combined with photolithography. Through the addition of photosensitive polymer into LTCC slurry, it was possible to form a microchannel in a ceramic body by UV photolithography. To realize the magnetic separation under the applied magnetic field in a continuous flow, the separation chamber was designed to have multi-channel system with different channel width. To check the performance of a ceramic-based microfluidic device, microfluidic parameters were optimized considering both the hydrodynamic and magnetic force of the ceramic-based chip.